Nervous system disruption and swimming abnormality in early-hatched pufferfish (Takifugu niphobles) larvae caused by pyrene is independent of aryl hydrocarbon receptors. Issue 2 (30th November 2017) - Itoyama, Tatsuya; Kawara, Moe; Fukui, Makiko; Sugahara, Yuki; Kurokawa, Daisuke; Kawaguchi, Masahumi; Kitamura, Shin-Ichi; Nakayama, Kei; Murakami, Yasunori
Abstract: Pyrene, a member of the polycyclic aromatic hydrocarbons (PAHs), contributes to abnormality in the size of the brain and the swimming behavior of pufferfish ( Takifugu niphobles ) larvae. We hypothesized that the aryl hydrocarbon receptor (AHR) may mediate pyrene-induced toxic effects because AHR is assumed to be a candidate for the downstream target of PAHs in many cases. To identify the contribution of AHR on developing pufferfish, we performed exposure experiments using β-naphthoflavone, an agonist of AHR. We found that the toxic effects of pyrene and β-naphthoflavone in pufferfish larvae are fundamentally different. Pyrene specifically induced problems in the developing midbrain and in swimming behavior, while β-naphthoflavone affected the heartbeat rate and the size of the yolk. These results suggest that the behavioral and morphological abnormality caused by pyrene exposure is mediated by an AHR-independent pathway. Alternatively, defects caused by pyrene may be attributed to the inhibition of the FGF signal. Highlights: We examine effects of pyrene and β-naphthoflavone on pufferfish larvae. Pyrene exposed larvae exhibit reduced brain size and abnormal swimming behavior. β-Naphthoflavone affected the heartbeat rate and the size of the yolk. The behavioral and morphological abnormalities caused by pyrene exposure are thought to be mediated by an AHR-independent pathway.